Nanosilica modulates C:N:P stoichiometry attenuating phosphorus toxicity more than deficiency in Megathyrsus maximus cultivated in an Oxisol and Entisol - de Faria Melo, Cíntia Cármen [UNESP]; Silva Amaral, Danilo [UNESP]; de Mello Prado, Renato [UNESP]; de Moura Zanine, Anderson; de Jesus Ferreira, Daniele; de Cássia Piccolo, Marisa (Springer Nature, 2023)
Silicon (Si) nanoparticles can attenuate nutritional disorders caused by phosphorus in forages through nutritional homeostasis. This paper aims to evaluate the effects of P deficiency and toxicity in Megathyrsus maximus cultivated in two types of soils and to verify whether Si application via fertigation can mitigate these imbalances. The following two experiments were carried out: cultivation of forage plants in pots with Entisol and Oxisol, in a 3 × 2 factorial design, with three nutritional levels of phosphorus (deficient, adequate, and excessive) and two Si concentrations in the irrigation water (0 and 1.5 mmol L−1). Height, number of tillers, rate of leaf senescence, dry matter production, C:N, C:Si, C:P, and N:P ratios; and C, P, and N use efficiencies were evaluated in two growth cycles. P imbalances hampered carbon assimilation, C:N:P homeostasis, and dry matter production. Nanosilica fertigation promoted silicon uptake, improving C:N:P homeostasis and nutritional efficiency in plants under P deficiency and toxicity. Leaf senescence was reduced with addition of Si in plants grown in Oxisol in the three nutritional states of P. Silicon attenuated the stress caused by P toxicity in Entisol and Oxisol, improving production in plants without nutritional stress in Oxisol. The supply of Si nanoparticles in the cultivation of M. maximus can contribute to a more efficient and sustainable use of phosphorus in pastures.